A note on the configuration of the digital ecosystem in Latin America - Ács, Zoltán J. (2022)
We evaluate the main characteristics of the digital ecosystem of North American (USA and Canada) and 16 Latin American economies for 2019. By employing the ‘benefit of the doubt’ model rooted in non-parametric techniques to scrutinize a composite indicator designed to assess the digital ecosystem (i.e., the Digital Platform Economy (DPE) index), the analysis allows the computation of endogenous (country-specific) weights that can be used for developing more informed policy making. The results show that countries prioritize different aspects of their digital ecosystem which confirms that, contrary to homogeneous prescription, tailor-made policy is a more desirable approach if the objective is to optimize the resources deployed to enhance the countries’ digital ecosystem.